It takes a village... Contending with drug shortages during disasters (2020)
The World Health Organization (WHO) designates access to essential drugs as a critical concern due to persistent shortages and escalating costs.1,2 Drug shortages are a function of demand and supply mismatches that can be affected by manufacturing, distribution, as well as regulatory, economic, or political considerations. Prior to the 2019 coronavirus disease (COVID-19) pandemic, numerous countries frequently documented such shortages, mostly with injectable drugs, to include antimicrobials, anaesthetics, cardiovascular and neurologic drugs, nutrition, electrolytes, and cancer chemotherapy.2,3 The COVID-19 pandemic dramatically demonstrates how large and sudden surge in demand can lead to shortages when local, national, and international supply chains cannot keep pace, in particular medications with limited therapeutic alternatives for critical care. We highlight the available literature on possible causes and mitigation strategies to manage shortages of critical care drugs from the local, institutional level to the global stage in a worldwide crisis such as a pandemic.